Perancangan Sistem Presensi Pengenalan Wajah Pada Sistem Tata Kelola Perkuliahan Universitas Atma Jaya Makassar - Adi Chandra Syarif (TEMATIKA: Jurnal Penelitian Teknik Informatika dan Sistem Informasi, 2021)
Course management system developed by University of Atma Jaya Makassar is providing an environment for course interactions within the classroom. One such interaction is attendance process done by the lecturer in the classroom. In this research, a camera-based attencance system is applied to a handheld device with facial recognition algorithm. The method used in this research is to do face recognition using a camera on a tablet PC so that students who can be recognized by their faces, can be declared present and stored data in the Course Management System (STKP).